2018
DOI: 10.3389/fped.2018.00171
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous COL4A3 Variants in Histologically Diagnosed Focal Segmental Glomerulosclerosis

Abstract: Introduction: Steroid-resistant nephrotic syndrome (SRNS) is one of the most frequent causes for chronic kidney disease in childhood. In ~30% of these cases a genetic cause can be identified. The histological finding in SRNS is often focal segmental glomerulosclerosis (FSGS). In rare cases, however, pathogenic variants in genes associated with Alport syndrome can be identified in patients with the histological finding of FSGS.Materials and Methods: Clinical information was collected out of clinical reports and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Previous reports on phenocopies come from cohorts or families with select disease groups such as AS, CAKUT, or ciliopathies. 13,14,16,[37][38][39] A recent study of 114 families with 138 adults (median age, 48 years) with CKD analyzed by using exome sequencing showed that in 21% of exome sequencing-solved cases, genetic analysis could "correct" the clinical diagnosis. Furthermore, in another study of 92 adults (all >18 years) with CKD, exome sequencing could "reclassify" the clinical diagnosis in 27% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on phenocopies come from cohorts or families with select disease groups such as AS, CAKUT, or ciliopathies. 13,14,16,[37][38][39] A recent study of 114 families with 138 adults (median age, 48 years) with CKD analyzed by using exome sequencing showed that in 21% of exome sequencing-solved cases, genetic analysis could "correct" the clinical diagnosis. Furthermore, in another study of 92 adults (all >18 years) with CKD, exome sequencing could "reclassify" the clinical diagnosis in 27% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…FSGS is an unspecific histologic phenotype shared by many kidney diseases, including hereditary nephropathies. 39,43 Therefore, it is not surprising that a genetically confirmed diagnosis of AS can present clinically as FSGS, especially if kidney biopsy is done late in the course of the disease (cases ATS-F9-II-1 and ATS-F261-II-1: kidney biopsy at ages 29 and 32 years, respectively). However, case ATS-F29-III-1 highlights that AS may only produce the histologic phenotype of minimal change disease, which in conjunction with the clinical phenotype of proteinuria may lead to the suspicion of hereditary FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several researches and cases reported that AS patients with COL4A5 mutations who have coinherited with COL4A3/COL4A4, MYO1E and LAMA5 mutations could exacerbated phenotypes (Lennon et al, ; Voskarides et al, ). These clinical symptoms occur mostly in the late disease stages and are thought to be secondary changes caused by primary GBM defects resulting from abnormalities in the collagen reticular structure (Braunisch et al, ). For these misdiagnosed patients, if treatment is conducted according to the classic glucocorticoid‐based regimen for FSGS, the treatment effect is not significant, and the patient may be considered to have hormone‐resistant nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…One proposal is that the ultrastructural changes induced by the collagen IV variants, perhaps under the influence of modifier genes such as laminin, result in impaired podocyte attachment to the glomerular basement membrane which leads to accelerated podocyte detachment, subsequent foot process effacement as a response to the increased shear stress induced by the denuded basement membrane and at a critical level of podocyte loss collapse of the capillary network with the appearance of the classical segmental sclerotic lesion (2,4,16). It also remains unclear as to whether the changes of FSGS are a secondary process occurring in those with TBMN or whether the collagen 4 variants are capable of causing primary FSGS (7,17). FSGS occurring as a secondary process to other basement membrane abnormalities may explain why immunosuppressive therapy has traditionally been less effective in inherited forms of FSGS, although there are case reports of the successful use of the calcineurin inhibitor cyclosporine for some patients harbouring inheritable collagen 4 disorders (6).…”
Section: Discussionmentioning
confidence: 99%